2022
DOI: 10.1080/21655979.2021.2021346
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ZFPM2-AS1 promotes retinoblastoma progression by targeting microRNA miR-511-3p/paired box protein 6 (PAX6) axis

Abstract: Long non-coding RNAs (lncRNAs) have been shown to play crucial roles in retinoblastoma progression. In this study, we aimed to investigate the mechanism of lncRNA ZFPM2-AS1 (ZFPM2-AS1) in retinoblastoma progression. Quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) and Western blotting assays were performed to determine the expression of lncRNA, microRNA (miRNA), mRNA, and protein. The changes in cell proliferation, apoptosis, and cell migration were assessed by functional experiments. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Functional experiments measured cell proliferation, apoptosis, and migration. Additionally, the luciferase assay validated the relation of ZFPM2-AS1, miR-511-3p, and PAX6 [ 43 ]. With the attention to confirm that PAX6 is modulated by miR-708a/miR-148, we firstly compared PAX6 levels in atrial water from HM patients and cataract patients by RT-qPCR and ELISA, which revealed elevated PAX6 in serum of neonatal retinopathy patients relative to healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…Functional experiments measured cell proliferation, apoptosis, and migration. Additionally, the luciferase assay validated the relation of ZFPM2-AS1, miR-511-3p, and PAX6 [ 43 ]. With the attention to confirm that PAX6 is modulated by miR-708a/miR-148, we firstly compared PAX6 levels in atrial water from HM patients and cataract patients by RT-qPCR and ELISA, which revealed elevated PAX6 in serum of neonatal retinopathy patients relative to healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of miRNA148a inhibited the expression of WNT1 protein in non-small cell lung cancer [ 27 ]; MIR-802 targeted MYLIP to inhibit the growth of cervical cancer cells [ 28 ]; and lncRNA SNHG3 regulated osteosarcoma invasion and migration through miRNA-151a-3p/RAB22A axis [ 29 ]. However, miRNAs are involved in far more cancers than these, including pancreatic cancer [ 30 ], retinoblastoma [ 31 ], melanoma [ 32 ], nasopharyngeal carcinoma [ 33 ], prostate cancer [ 34 ], bladder cancer [ 35 ], and breast cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…NRIR , ZFPM2-AS1 , and LINC01215 expression levels were down-regulated in si LGALS1 HEMECs. ZFPM2-AS1 has been shown to play crucial roles in the progression of retinoblastoma, an angiogenesis-associated disease [ 45 ]. The interferon (IFN) family of cytokines serves as pivotal regulators of angiogenesis [ 46 ], while NRIR was found to be a negative Regulator of IFN Response [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%